Sistem Pendukung Keputusan untuk Menentukan Mutasi Personel POLRI pada POLSEK Galang Menggunakan Metode Analytic Hierarchy Process (AHP). - Rizky Perdana; R.Fanry Siahaan (CV. Utility Project Solution, 2022)
Abstract-In order to meet the need for professional and proportional human resources or in terms of the right person in the right place and the right job in accordance with their scientific fields, especially in the police organization, mutations can be carried out. The goal is that members of the Indonesian National Police obtain deep job satisfaction and can provide maximum work performance to the Indonesian National Police or in other words to realize the implementation of a planned, directed, objective, and fair process of personnel career development. To fulfill the element of professionalism, it is necessary to have a system of eligibility for the transfer of police personnel. The determination of the mutation of the Indonesian National Police will be studied using the Decision Support System with the Analytical Hierarchy Process (AHP) method. Mutations of Polri personnel at the Galang Police Station are only at the BRIPTU rank. With three alternative data and six criteria, namely length of service, work performance, responsibility, education, communicative and special skills. Based on data processing against predetermined criteria, it can be concluded that Polri personnel on behalf of Agung Parkoso will be transferred with a weight value of 0.160. Keywords- Analytical Hierarchy Process (AHP), Police Personnel Mutation, Decision Support System Abstrak- Guna memenuhi kebutuhan sumber daya manusia yang yang professional dan proposional atau dengan istilah the right person in right place and the right job sesuai dengan bidang keilmuanya khususnya dalam organisasi polri dapat dilakukan dengan mutasi. Tujuanya agar para anggota polri memperoleh kepuasan kerja yang mendalam dan dapat memberikan prestasi kerja yang maksimal kepada Kepolisian Republik Indonesia atau dengan kata lain untuk mewujudkan terselenggaranya proses pembinaan karir personel yang terencana, terarah, objektif, dan berkeadilan. Untuk memenuhi unsur keprofesionalan tersebut diperlukan adanya sistem kelayakan pemutasian personil polri. Penentuan mutasi polri ini akan dikaji dengan menggunakan Sistem Pendukung Keputusan metode Analitycal Hierarchy Process (AHP). Mutasi personel Polri di Polsek Galang hanya pada pangkat BRIPTU. Dengan tiga data alternatif dan enam Kriteria yakni lama menjabat, Prestasi Kerja, Responsibility, Pendidikan, Komunikatif dan Keterampilan Khusus. Berdasarkan pengolahan data terhadap Kriteria yang sudah ditentukan, maka dapat dihasilkan bahwa personil Polri atas nama Agung Parkoso yang akan dimutasi dengan nilai bobot sebesar 0,160. Kata Kunci- Analitycal Hierarchy Process (AHP), Mutasi Personil Polri, Sistem Pendukung Keputusan